The Advantages of the Buttonhole Technique. A Case Report in a Dialysis Center in Puglia. Issue 1 (January 2016) - Quaranta, Patrizia; Nuccio, Luigi; Alessio, Marianeve; Alfarano, Anna Maria; Carluccio, Ambrogio; Melcarne, Loredana; Nuccio, Maria Rosaria; Quarta, Tonia; Schirinzi, Antonella; Nuzzo, Vitale
Native AVF represents the best vascular access for patients undergoing chronic hemodialysis treatments. Accordingly to KDOQI 2006, constant site cannulation technique (or butthonhole, BH) can reduce infiltration events, cannulation pain, make self cannulation process easier and maintain a better vein outflow integrity. Nursing staff need to be trained in order to acquire and improve AV cannulation skills. The objective of this study is to demonstrate benefits of buttonhole technique for AVF cannulations in chronic hemodialysis patients by a case report experience in our centre. Based on our experience, only if adequate training will be provided to nursing staff and greater emphasis will be given to patients empowerment and AV self management, BH technique could bring greater advantages and less complications for both patients and staff. BH technique, if properly applied, can reduce infiltration risk, bleeding and pain while preserving vein physiology.